Intestinal Parasitic Infection, The Use of Latrine, and Clean Water Source In Elementary School Children At Coastal And Non-Coastal Areas, Sumenep District, Indonesia - Renaldy, Raden Bagus Yanuar; Aflahudin, M. Ahda Naufal; Salma, Zukhaila; Sumaryono, Sumaryono; Fitriah, Muhammad Yasin; Sulistyawati, Sri Wijayanti; Husada, Dominicus; Basuki, Sukmawati (Institute of Topical Disease Universitas Airlangga, 2021)
Inadequate latrine and water source cause transmission of intestinal parasitic infection, particularly in children. There is a lack information about it and it is needed to be investigated. This study aimed to compare the prevalence of intestinal parasitic infection, the use of latrine and clean water source in elementary school children at coastal and non-coastal areas in Sumenep District, Indonesia. An analytic observational study with cross sectional design was conducted in Dasuk Timur Elementary School located at coastal area, and Kolor II Elementary School at non-coastal area, Sumenep district, in January 2020. Intestinal parasites in students' stools were identified by microscopic examination using wet direct smear stained with lugol. The use of latrine and water sources were analyzed with questionnaire. A total of 68 children stools were collected from both elementary schools. Worm infections were not found. Thirty-one children (31/44, 70.5%) from Dasuk Timur Elementary School and eight children (8/24, 33.3%) from Kolor II Elementary School were infected with intestinal protozoan and significant difference (P=0.003, Chi-square test). Blastocystis hominis was highly found in stools of Dasuk Timur Elementary School's students (31/44, 70.5%) and significantly different from Kolor II Elementary School's students (P<0.0001, Chi-square test). Three children (3/44, 6.8%) from Dasuk Timur Elementary School were still practicing open defecation. Dasuk Timur Elementary School's students suffered from intestinal parasitic infection were mostly using non-piped water source (20/31, 64.5%) and were significantly different between two elementary schools (P=0.015, Fisher's exact test). Prevalence of intestinal parasitic infections in children was found higher in coastal than non-coastal area due to the commonly use of unclean water sources and inadequate latrine.